Монументальная пропаганда: [роман] / Владимир Войнович ; [художник А. Анно] - Войнович Владимир Николаевич (Изограф, 2000)
Экземпляры: аб. (2001) / Инвентарный номер: 43373 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: В 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44